A novel potentiometric biosensor for determination of L-lysine in commercial pharmaceutical L-lysine tablet and capsule - Yarar, Saniye; Karakus, Emine (TAYLOR & FRANCIS LTD, 2016)
The construction of an L-lysine biosensor on ammonium-selective poly(vinylchloride) (PVC) membrane electrode is described in this study. The construction procedure occurs in two stages: (I) the preparation of ammonium-selective poly(vinylchloride) (PVC) membrane electrode and (II) the chemical immobilization of lysine oxidase on this ammonium-selective electrode by using glutaraldehyde. The ammonium ions produced after enzymatic reaction were determined potentiometrically. The sensitivity of the lysine biosensor against ammonium ions and lysine were studied. The response time, linear working range, reproducibility and life time of the biosensor were also determined. The interfering effect of other amino acids on the biosensor performance was also studied and potentiometric selectivity coefficients were calculated. Although the biosensor responded mainly against tyrosine, a lot of amino acids and ascorbic acid that can be present in some real samples did not show any important interference. Additionally, lysine assay in commercial pharmaceutical lysine tablets and capsules was also successfully carried out. The results were in good agreement with previously reported values.
Keywords: lysine oxidase; enzyme electrode; potentiometric; lysine determination; lysine biosensor; AMPEROMETRIC BIOSENSOR; PRECOLUMN DERIVATIZATION; LIQUID-CHROMATOGRAPHY; OXIDASE; MEMBRANE; FEEDS; FOOD; Biotechnology & Applied Microbiology; Engineering; Materials Science